2020
DOI: 10.1177/0846537120904452
|View full text |Cite|
|
Sign up to set email alerts
|

Etiology of Burnout in Canadian Radiologists and Trainees

Abstract: Purpose: There is worsening of burnout symptoms experienced by radiologists and trainees. We explored potential factors that exacerbate burnout symptoms observed in the Canadian radiological community and currently available protective factors as next steps for establishing viable solutions for burnout. Methods: An 11-question electronic survey was distributed to Canadian radiologists and trainees through the Canadian Association of Radiologists (CAR). Approval from a local ethics board and the CAR were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 19 publications
(23 reference statements)
1
19
0
Order By: Relevance
“…However, radiologists felt that their concerns were not being heard at a systemic level. 2 This study was in agreement with a previous study that also reported high levels of burnout in Canadian radiology residents (51%) and identified poor work-life balance and harassment or intimidation as major stressors. 3 This work was performed before the COVID-19 pandemic hit.…”
Section: Introductionsupporting
confidence: 93%
“…However, radiologists felt that their concerns were not being heard at a systemic level. 2 This study was in agreement with a previous study that also reported high levels of burnout in Canadian radiology residents (51%) and identified poor work-life balance and harassment or intimidation as major stressors. 3 This work was performed before the COVID-19 pandemic hit.…”
Section: Introductionsupporting
confidence: 93%
“…The consequences of burnout are not limited to the health of the workers, but also affect the quality of care provided and organisational well-being. 14 , 15 The prevalence of burnout syndrome had already increased in most Western countries even before the pandemic as a result of high levels of stress and the constant increase in workload. 16 , 17 , 18 , 19 , 20 It may well be that the COVID-19 pandemic has exacerbated an existing problem within generally overburdened health systems, thus increasing the prevalence of this syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the article by Zha and colleagues 1 on radiologists’ and radiology trainee burnout. Of note, their study became available online on Feb 28, 2020, immediately before the onset of the COVID-19 pandemic in Canada.…”
mentioning
confidence: 99%